Corporate Social Responsibility Disclosure and Cost of Equity: Evidence From Public Listed Companies in Malaysia - Mohd Waliuddin, Mohd Razali; Tracia, Sim; Damien Iung Yau, Lee; Fatin Nur Hidayah, Taib Khan; Shazali, Shaharuddin (UNIMAS Publisher, 2023)
Corporate social responsibility (CSR) has been rolledout in recent years as it has become vital owing to the massive growth of financial institutions, mutual funds, online resources, and other publications. CSRdisclosure could reduce the cost of equity. The study's main objective is to investigate the CSR disclosure by companies listed in Malaysia towardsthe cost of equity. This study is based on three hundred four (304) samples of Malaysian listed companies from 2013 to 2014. The data of the sampleswere mainly collected from annual reports, except for financial data which were collected from DataStream. The result revealed that the CSR disclosure in the annual report could reduce the company's cost of equity by reducinginformation asymmetry, reducing agency costs, and reducing companies' risk. The result also shows that liquidity has a significant negative relationship with the cost of equity. The higher information disclosure enhances stock market liquidity,thus, reducing the cost of equity through the reduction of risk as well increasing demand for a company's securities. The size, liquidity, and growth have a significant relationship with the cost of equity.